First deployment of IoT tracking devices on Common swift Apus apus: a pilot study (Avocetta, 2024)
Five breeding adults of Common swift Apus apus from a north Italian colony were equipped with lightweight (1.2 g) tracking devices based on IoT (Internet of Things) technology, collecting location data and transmitting them through the Sigfox network of base stations. The main novelty is that these devices enable the real-time transmission of locations with no need for re-capturing. The devices were glued to the back feathers, which were to be lost during moult at the latest. The devices transmitted over variable periods (3-25 days, mean ± SD: 9.31 ± 11.8), collecting in total a mean ± SD of 17.58 ± 18.4 locations per individual. These data mostly recorded movements around the colony, except for one bird that migrated immediately after tagging. This bird was successfully tracked until reaching southern Spain, where transmissions ended because the IoT network is not available out of continental Europe, with a few exceptions. This pilot study demonstrates that swifts can be successfully tagged with lightweight devices without harnessing. While single-direction migration displacements can be successfully tracked over the EU with these devices, researchers need improvements in both the location quality of the Sigfox IoT network and the life length of the devices if they aim to study the details of foraging movements. Eventually, we stress that beyond pure research purposes, tracking swifts through IoT devices—which transmit real-time data to the Animal Tracker mobile app—may also effectively engage the public and enhance conservation awareness.
Keywords: tracking; IoT devices; movement ecology; bio-logging; Apus apus